2021
DOI: 10.1136/bmjopen-2021-050427
|View full text |Cite
|
Sign up to set email alerts
|

Misconceptions about COVID-19 among older Rohingya (forcefully displaced Myanmar nationals) adults in Bangladesh: findings from a cross-sectional study

Abstract: ObjectivesDue to low health literacy and adverse situation in the camps, there are possibilities of misconceptions related to COVID-19 among the older Rohingya (forcefully displaced Myanmar nationals or FDMNs) adults in Bangladesh. The present research aimed to assess the level of misconceptions and the factors associated with it among the older FDMNs in Bangladesh.DesignCross-sectional.SettingA selected Rohingya camp situated in Cox’s Bazar, a southeastern district of Bangladesh.ParticipantsInformation was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…We did not find any single study on older refugees in Bangladesh and other countries to compare this finding with. However, existing studies conducted among younger Rohingya refugees in Bangladesh, 19 child refugees in England, 29 refugees and asylum seekers in Switzerland 30 and Syrian refugees in Germany 31 reported several barriers associated with refugees’ access to medicine and routine healthcare, including poor literacy of older refugees, 19 language and legal barriers and travel costs. 32 Furthermore, several studies indicated that limited long-term clinical care facilities for older individuals, limited/unavailability of medicines, inadequate knowledge about available services and healthcare system, inadequate ‘cultural competence of the healthcare providers, age-related self-stigma and financial constraints were the primary reasons that refugees experienced difficulties in accessing medical services.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We did not find any single study on older refugees in Bangladesh and other countries to compare this finding with. However, existing studies conducted among younger Rohingya refugees in Bangladesh, 19 child refugees in England, 29 refugees and asylum seekers in Switzerland 30 and Syrian refugees in Germany 31 reported several barriers associated with refugees’ access to medicine and routine healthcare, including poor literacy of older refugees, 19 language and legal barriers and travel costs. 32 Furthermore, several studies indicated that limited long-term clinical care facilities for older individuals, limited/unavailability of medicines, inadequate knowledge about available services and healthcare system, inadequate ‘cultural competence of the healthcare providers, age-related self-stigma and financial constraints were the primary reasons that refugees experienced difficulties in accessing medical services.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed method of the study is presented elsewhere. 19 The inclusion criteria included age ≥60 years and Rohingya Forcibly Displaced Myanmar Nationals (FDMN) status. Participants were excluded if they self-reported having any of the following criteria: adverse mental conditions (clinically diagnosed schizophrenia, bipolar mood disorder, dementia/cognitive impairment), a hearing disability or were unable to communicate with researchers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, certain compound comorbidities, which are prevalent in displaced populations, impact the clinical progression of COVID-19, but this impact is poorly quantified 41 42. Similarly, under-reporting of COVID-19 cases and deaths is a concern in many countries and settlements due to inadequate disease surveillance infrastructure43 and the spread of misinformation 44 45. To address this, SB modelling can be a powerful approach to explore possible futures under uncertainty.…”
Section: Challengesmentioning
confidence: 99%
“…Older adults from the refugee background may be particularly vulnerable to increased mental health conditions during this pandemic [ 22 ] with a possible increase in tobacco use and chronic disease episodes. While a few recent studies [ 23 , 24 ] have documented adverse mental health issues among the Rohingya older adults, no research has reported their tobacco use patterns amid this pandemic. Therefore, the present research aimed to explore the perceived change in tobacco use and the factors associated with this change among older adults residing in the Rohingya refugee camps during this COVID-19 pandemic in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%